2014
DOI: 10.2478/s11756-013-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Caralluma tuberculata and evaluation of antioxidant potential

Abstract: Present study describes rapid in vitro propagation of Caralluma tuberculata, a traditional medicinal plant, and antioxidant potential of calli and plants extracts. The highest callus induction rate (93.3%) with maximum weight of calli 5.2 g was achieved from shoot tip explants on MS medium supplemented with 9.04 µM 2,4-D and 4.44 µM BA. The maximum shoot induction rate (71.1%) with mean number of shoots 3.66 ± 1.53 and 4.6 cm average shoot length was observed on 13.32 µM BA, 4.52 µM 2,4-D and 2.89 µM GA3 appen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…The ethanolic extract of the plant showed moderate nitric oxide scavenging activity at a concentration of 60 mg when compared to gallic acid as a standard. Rehman et al [46] reported the antioxidant properties of different extracts of C. tuberculate. Jerome et al [47] reported the phytochemical constituents in C. umbellate, also suggesting that this genus has high pharmacological potential.…”
Section: Free-radical-scavenging Activitiesmentioning
confidence: 99%
“…The ethanolic extract of the plant showed moderate nitric oxide scavenging activity at a concentration of 60 mg when compared to gallic acid as a standard. Rehman et al [46] reported the antioxidant properties of different extracts of C. tuberculate. Jerome et al [47] reported the phytochemical constituents in C. umbellate, also suggesting that this genus has high pharmacological potential.…”
Section: Free-radical-scavenging Activitiesmentioning
confidence: 99%
“…Nikam et al (2007) reported the highest percentage of rooting, number of roots and root length in C. hirsuta, when the nodal explants derived in vitro shoots were cultured on the half strength MS medium fortified with 2.0 µM IAA. When the microshoots of Caralluma tu berculata were cultured on half strength MS medium supple mented with 5.07 µM IAA, they were produced 3.0±0.15 roots/microshoot (Rehman et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Caralluma species have been used by humans as tonic, carminative, anti-helminthic and anti-tumor agent. 8 Caralluma is reported to be effective in rheumatism and also known to have hypotensive effect. 9,10 The phytochemical constituents include volatile alkaloids, cardiac glycosides, flavonoids, saponins, sterols and tannins.…”
Section: Caralluma Tuberculata Which Belongs To Familymentioning
confidence: 99%